Quality Improvement of Fruit Melon Varieties (Cucumis Melo L.) With Ab Mix Nutrition Formulation - Supriyanta, Bambang; Kodong, Frans Richard; Widowati, Indah; Siswanto, Farida Ariefa (RSF Conference Series: Engineering and Technology, 2022)
Melon (Cucumis melo L.) is a horticultural commodity that has high economic value. The sweet taste, thick flesh, crunchy texture and high quality are the reasons people are interested in melon. The increase in melon productivity can be supported by the use of superior seeds and cultivation with a hydroponic system. The purpose of this research were to obtain premium melon with high quality which are characterized by sweetness levels above 15 brix, attractive skin and flesh color, high vitamin C content, and fruit flesh thickness. The study was conducted in March to July 2021 in greenhouse CV. Agroniaga. This study used a Completely Randomized Design (CRD) with 8 treatments: N1 (Formulation 1), N2 (Formulation 2), N3 (Formulation 3), N4 (Formulation 4), N5 (Formulation 5), N6 (Control 1 AB mix Nutriponic ), N7 (Control 2 AB mix Goodplant), and N8 (Control 3 General). Quantitative data were analyzed by analysis of variance at the 5% level. If there is a significant difference between treatments, the further test is continued with the Duncan multiple range test at a significance level of 5%. Qualitative observation data will be analyzed with descriptive statistics. Result of this research showed that N3 formula is the best to increase both harvest and quality of fruit.